Analysis Of Health Promotion Implementation In Pulmonary Tuberculosis Disease Control In Puskesmas Harapan Raya Kota Pekanbaru 2022: Analisis Pelaksanaan Promosi Kesehatan Dalam Pengendalian Penyakit Tuberkulosis Paru Di Puskesmas Harapan Raya Kotapekanbaru Tahun 2022 - Feby Fitriani; Syukaisih Syukaisih; Winda Septiani (Badnur Medisa Group, 2022)
Pulmonary Tuberculosis is an infectious disease caused by the bacterium Mycobacterium Tuberculosis which can attack various organs, especially the lungs. According to data from the Harapan Raya Health Center in 2020 there were 63 TB cases, in 2021 there were 73 TB cases, a total of 136 cases of people affected by pulmonary TB. This study aims to determine the implementation of health promotion in the control of pulmonary tuberculosis. This research uses a qualitative type of research with an in-depth observation and interview design. Informants were determined by purposive sampling technique Research variables are empowerment, advocacy and partnership. The research informants were 7 people, 1 key informant, namely the head of the Harapan Raya Health Center, 2 main informants, namely the person in charge of health promotion and the person in charge of tuberculosis. and 4 supporting informants, namely 2 general public people and 2 TB patients. Data collection was carried out in the work area of puskesmas Harapan Raya through in-depth interviews and observations. Data management techniques with triangulation. The results of this study indicate that empowerment is less than optimal due to the wide working area of ​​the Harapan Raya Health Center so that the empowerment is not evenly distributed, advocacy in TB control is still lacking because the budget for TB control still expects only a small amount of BOK funds and lack of support from community leaders in finding suspects TB case. Partnerships in TB control have been implemented. It is hoped that the Harapan Raya Health Center will further increase Health empowerment, advocacy and partnerships in tb control programs.